Editor in Chief - Aktaria, Erma (Indonesian Journal of Engineering and Computer Science, 2015)
Abstrak AbstrakAbstrakAbstrakAbstrakAbstrakAbstrakAbstrakAbstrakAbstrakAbstrakAbstrakAbstrakAbstrakAbstrakAbstrakAbstrakAbstrakAbstrakAbstrakAbstrakAbstrakAbstrakAbstrakAbstrakAbstrak Abstrak AbstrakAbstrakAbstrakAbstrakAbstrakAbstrakAbstrakAbstrakAbstrakAbstrakAbstrakAbstrakAbstrakAbstrakAbstrakAbstrakAbstrakAbstrakAbstrakAbstrakAbstrakAbstrakAbstrakAbstrakAbstrakAbstrak AbstrakAbstrakAbstrakAbstrakAbstrakAbstrakAbstrakAbstrakAbstrakAbstrakAbstrakAbstrakAbstrakAbstrakAbstrakAbstrakAbstrakAbstrakAbstrakAbstrakAbstrakAbstrakAbstrakAbstrakAbstrakAbstrak AbstrakAbstrakAbstrakAbstrakAbstrakAbstrakAbstrakAbstrakAbstrakAbstrakAbstrakAbstrakAbstrakAbstrakAbstrakAbstrakAbstrakAbstrakAbstrakAbstrakAbstrakAbstrakAbstrakAbstrakAbstrak